Comparison of Cerebral Malaria Mice Models Infected by P. berghei ANKA - Prawesty Diah Utami; R. Varidianto Yudo Tjahjono; Indi Jazilah; Ismy Azizah Sisnawati (Denta Journal Kedokteran Gigi, 2020)
The high morbidity and mortality due to malaria infection makes it a global health problem. The pathogenesis and pathophysiology of cerebral malaria has not been fully understood. The use of cerebral malaria model mice is one alternative to understand its pathogenesis and pathophysiology. The purpose of this study was to compare Swiss mice and C57BL / 6 mice inoculated by P.berghei ANKA as a model of cerebral malaria mice. Methods: The study design was a randomized Post Test Control Only Group Design using 12 Swiss mice and 12 C57BL / 6 mice divided into 2 groups each: the treatment group inoculated by P. berghei ANKA and the control group without inoculation. Observation of clinical manifestations and parasitemia level was carried out from day 1 to day -10. The study results showed that K2 group showed a significant increase in the degree of parasitemia compared to K4. K4 group showed clinical manifestations of cerebral malaria while K2 did not show clinical manifestations of cerebral malaria. Conclusion: C57BL / 6 mice inoculated by PbA can be used as cerebral malaria animal models.